Exploring Connections between Writing Methods Teacher Education Courses and K-12 Field Experience. (2nd October 2019) - Myers, Joy; Sanders, Jennifer; Ikpeze, Chinwe H.; Yoder, Karen K.; Scales, Roya Q.; Tracy, Kelly N.; Smetana, Linda; Grisham, Dana L.
ABSTRACT: The purpose of this study was to understand how writing teacher educators, who used research-based practices, make connections to K-12 classrooms for their preservice teacher candidates. A team of eight literacy researchers and educators from institutions across the United States collaborated to conduct a qualitative interview study of 15 writing teacher educators. This study is grounded in literature on effective writing instruction as well as university and K-12 connections, and it is framed by Kolb's experiential learning theory. Findings suggest several themes related to how writing teacher educators make connections to K-12 classrooms including intentional field experiences, spending time in the field themselves, connecting their teaching of writing assessment to actual classrooms and students, and engaging in consistent reflection and revision of their courses. Implications and future directions for research are explored.